Melanoma mortality in the capitals of Northeast Brazil, 2001-2017: analysis by the regression model by inflection points - Amanda Maria Sandes Lemos; Beatriz Gomes de Castro; André Luis Oliveira do Nascimento; Carlos Alberto de Oliveira Rocha; João Paulo Oliveira de Almeida; Gustavo Nascimento Monteiro Siqueira; Myllena Vitória Bispo Santana; João Vitor Bispo Santana; Tânia Rita Moreno de Oliveira Fernandes; Maria Deysiane Porto Araújo; Thaysa Kelly Barbosa Vieira Tomé; José Roberto Amorim; et al. (Sociedade Brasileira de Dermatologia (SBD), 2022)
Introduction: Melanoma comprises 3% of all skin tumors and can produce metastasis with high mortality. Objective: To analyze the temporal behavior of mortality from skin melanoma in the capitals of Northeast Brazil from 2001 to 2017. Methods: We conducted an ecological time series study involving all deaths due to melanoma registered in the capitals of the Northeast region of Brazil from 2001 to 2017. Crude and standardized rates by the world and Brazilian populations were analyzed. We obtained the indicators from the National Cancer Institute (INCA).The regression model by inflection points was used in the statistical analysis, calculating the annual variation and the average annual variation percentages. Results: There were 954 deaths from melanoma.The three rates analyzed showed a linear growth trend over the time series: proportional mortality increased from 2.1% to 8.28% (AAPC 6.0%; p<0.02), the crude mortality grew from 0.22 to 0.64/100 thousand (AAPC 5.0%; p<0.01) and the mortality adjusted by the world population in the capitals of the Northeast rose from 0.28 to 0.61/100 thousand (AAPC 2.7%; p<0.01). Conclusion: Mortality from melanoma grew in the Northeastern capitals, with inequality between the sexes and according to the capitals.